Solving mathematical word problems using dynamic assessment for scaffolding construction - Andi Saparuddin Nur; Kartono Kartono; Zaenuri Zaenuri; Rochmad Rochmad (Institute of Advanced Engineering and Science, 2022)
Students need the ability to solve word problems can connect mathematics with the context of everyday life. However, students experience many difficulties and need assistance in the form of scaffolding can to solve word problems well. Dynamic assessment is an alternative approach to constructing the form of scaffolding that student need to solve mathematical word problems. This study aimed to analyze the students' difficulties in solving word problems and the required form of scaffolding through dynamic assessment. The subjects of this study consisted of 177 students spread across 10 public junior high schools in Jeneponto Regency, South Sulawesi Province, Indonesia. There was a four-word problem tested and analyzed using dynamic assessment. Student solutions were grouped based on the type and form of scaffolding needed: level 5 (no solution), level 4 (without analysis/unrepresentative), level 3 (computational error), level 2 (incomplete procedure), level 1 (lack of thoroughness in the final stage). The form of scaffolding is constructed to help students solve mathematical word problems step by step at each level. The use of scaffolding accompanied by instructions helps students develop word problem-solving skills. Dynamic assessment can be considered to be integrated with the mathematics learning process that supports scaffolding construction to solve students' word problems.